Current and novel approaches to children and young people with congenital adrenal hyperplasia and adrenal insufficiency. Issue 3 (June 2015) - Webb, Emma A.; Krone, Nils
<x xml:space="preserve">Abstract</x> Congenital adrenal hyperplasia (CAH) represents a group of autosomal recessive conditions leading to glucocorticoid deficiency. CAH is the most common cause of adrenal insufficiency (AI) in the paediatric population. The majority of the other forms of primary and secondary adrenal insufficiency are rare conditions. It is critical to establish the underlying aetiology of each specific condition as a wide range of additional health problems specific to the underlying disorder can be found. Following the introduction of life-saving glucocorticoid replacement sixty years ago, steroid hormone replacement regimes have been refined leading to significant reductions in glucocorticoid doses over the last two decades. These adjustments are made with the aim both of improving the current management of children and young persons and of reducing future health problems in adult life. However despite optimisation of existing glucocorticoid replacement regimens fail to mimic the physiologic circadian rhythm of glucocorticoid secretion, current efforts therefore focus on optimising replacement strategies. In addition, in recent years novel experimental therapies have been developed which target adrenal sex steroid synthesis in patients with CAH aiming to reduce co-morbidities associated with sex steroid excess. These developments will hopefully improve the health status and long-term outcomes in patients with congenital adrenal hyperplasia and adrenal insufficiency.